(untitled) (Raparin Journal of Humanities (RJH), 2024)
This paper, titled "The Impact of Alai Suri (Red Flag) Kurdayeti Magazine on the Propagation of National Awareness," delves into an examination of the content within Alai Suri Kurdayeti Magazine during the period of the mountain struggle and the revolutionary era, spanning from 1981 to 1982. Despite the protracted history of the Kurdish people’s struggle for their national rights, the establishment of a comprehensive national identity remains an indispensable intellectual and vital requirement within Kurdish society, intrinsically tied to the notion of national consciousness. The manifestation of a national identity fundamentally hinges on shared national principles, a common language, culture, religion, history, collective aspirations, and unified political and legal principles, all of which necessitate a heightened state of national consciousness. Throughout the history of the Kurdistan liberation movement, diverse strategies have been employed to attain this identity, with media engagement serving as one prominent avenue. During a particularly sensitive period in Kurdish history within South Kurdistan (1981-1982), the Kurdish Socialist Party (PASOK) issued Alai Suri Kurdayeti Magazine. This publication, apart from accomplishing its political objectives, aimed to acquaint Kurdish society with various facets of life and intellect. Its purpose was to cultivate national thought and consciousness while alerting the community to the imminent threats they faced.